In situ AP-XPS analysis of a Pt thin-film sensor for highly sensitive H2 detection. Issue 70 (31st July 2020) - Toyoshima, Ryo; Tanaka, Takahisa; Kato, Taro; Uchida, Ken; Kondoh, Hiroshi
Abstract : Changes in surface chemical state of a resistivity-based Pt thin-film sensor for H2 gas were observed under working conditions with direct in situ spectroscopy. Abstract : In situ ambient-pressure X-ray photoelectron spectroscopy (AP-XPS) combined with resistivity measurement was performed for a Pt thin-film H2 gas sensor. We experimentally demonstrate that the chemical state of the Pt surface changes under working conditions, and it directly links to the sensing performance. Moreover, the operating principle is discussed at the atomic scale.